Calligraphic woodcarving ornamentations in selected Peninsular Malaysian mosques / Ahmadreza Saberi - Saberi, Ahmadreza (Institute of Graduate Studies, UiTM, 2017)
Woodcarving is a form of Malaysian traditional art. After the advent of Islam in the Malay Peninsula in the 13th century (Pasai) and 14th century (Malacca), Islamic motifs such as calligraphic woodcarvings are added to the local art forms, particularly to embellish Malaysian mosques. Although Malaysian mosques have been built using three architectural styles, namely the vernacular, colonial and modern, the designers did not distinguish between the styles when installing calligraphic woodcarving ornamentations in the prayer halls. Furthermore, although many studies have been conducted to investigate the characteristics of Malaysian woodcarvings, findings on the opinions of mosque users are lacking. Hence, this thesis aims to identify the various forms of calligraphic woodcarving ornamentations through the analysis of their writing styles and other characteristics of this ornamentation from the selected peninsular Malaysian mosques. The objectives are: i) to establish the judgments of mosque users about calligraphic woodcarving ornamentations based on types of scripts, legibility, locations, function, aesthetic, desirability and combination of patterns; ii) to analyse the current calligraphic woodcarving ornamentation (writing styles, locations and contents) of Malaysian mosques; and iii) to propose recommendations on the appropriate design of calligraphic woodcarving ornamentations for Malaysian mosques. This study employed quantitative and qualitative methodologies…